A physical and physiological study of blowing technique in recorder playing - Bak, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
The research summarized in this paper has revealed some of the specific physiological conditions of recorder playing. In order to understand the nature of the instrument it is essential to be aware of these physiological conditions, although they seem to have been largely neglected by pedagogues. It appeared during the investigation that registration of blowing pressure raises a number of problems. The author succeeded in identifying some of the specific causes of measurement error, and the paper describes an approach which makes it possible to detect such errors. The measurement errors encountered were found to provide interesting information on the technique used by the individual recorder player.